Two dimensional ferromagnetic semiconductor: monolayer CrGeS3. (10th October 2019) - Ren, Yulu; Ge, Yanfeng; Wan, Wenhui; Li, Qiaoqiao; Liu, Yong
Abstract: Recently, two-dimensional ferromagnetic semiconductors have been an important class of materials for many potential applications in spintronic devices. Based on density functional theory, we systematically explore the magnetic and electronic properties of CrGeS3 with the monolayer structures. It is found that the bandgap of spin-up state is 1.01 eV when it is 1.07 eV in spin-down state. The exchange splitting is calculated as 0.67 eV (2.21 eV by HSE06 functional), which originates from bonding hybridized states of Cr e g -S p and unoccupied Cr t 2 g -Ge p hybridization. After that, the comparison of total energy between different magnetic states ensures the ferromagnetic ground state of monolayer CrGeS3 . The reason of the magnetic states originates mainly from the competition between antiferromagnetic direct neighboring Cr–Cr exchange and ferromagnetic superexchange mediated by S atom. And the results also show the magnetic moment of 6 per unit cell, including two Cr atoms. Besides, we estimate that the monolayer CrGeS3 possesses the Curie temperature of 161 K by mean-field theory. The results suggest that monolayer CrGeS3 crystals will possess potential applications in nanoscale spintronics.